2016
DOI: 10.1128/jcm.03014-15
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Clostridium difficile Infections in Children

Abstract: The detection and diagnosis of Clostridium difficile infection in pediatric populations have some unique considerations in comparison to testing in adults. The testing methodologies, including toxigenic culture, cell cytotoxicity, antigen detection, and, more recently, molecular testing, are the same in all age groups. However, limited data exist on the specific performance characteristics in children. In this review, we focus on the challenges of testing in pediatric populations and assess the available data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Severe complications of CDI, such as fulminant CDI or pseudomembranous colitis, are not common among children [ 16 18 ]. Neither Antonara et al [ 17 ] nor Chakrabarti et al observed severe CDI or death attributing to CDI [ 20 ]. Contrary, in the other study of 37 patients, the increased risk of death was evaluated at 180 days and restricted to patients with severe CDI (57% of patients) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe complications of CDI, such as fulminant CDI or pseudomembranous colitis, are not common among children [ 16 18 ]. Neither Antonara et al [ 17 ] nor Chakrabarti et al observed severe CDI or death attributing to CDI [ 20 ]. Contrary, in the other study of 37 patients, the increased risk of death was evaluated at 180 days and restricted to patients with severe CDI (57% of patients) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe CDI course was defined by CDI first-line treatment failure which meant lack of improvement in stool consistency after 3 days, the need to add the second drug, new signs of severe colitis, the need of admission to an intensive care unit, and/or death related to CDI [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…[20] In older children, increasing CDI rates have been documented in some settings. [20,21] This study has demonstrated that the overall reported CDI incidence rate decreased with the introduction of a two-step algorithm for laboratory diagnosis of CDI. Standardisation of laboratory testing methodology and CDI incidence rate reporting is required in order to yield robust data.…”
Section: Research Discussionmentioning
confidence: 91%
“…As a discussion of C difficile testing is outside the scope of this article, the authors refer readers to a review of C difficile testing in pediatrics. 40…”
Section: Detection Of Gastrointestinal Pathogensmentioning
confidence: 99%